الأثر الدلالي للتعريف والتنكير في القرآن الكريم: دراسة تطبيقية - الفضلى، وضحة عواد (جامعة عين شمس - كلية الآداب, 2018)
تعد دراسة ظاهرة التذكير والتأنيث من الدراسات النحوية الهامة، لما لها من أثر كبير في تركيب الجملة، وهي مطلب ضروري لدى المتخصصين في الدراسات اللغوية، ولأهمية هذه الظاهرة فقد حظيت باهتمام علماء اللغة، وهي ظاهرة محل اتفاق بين العلماء، وكان لذلك الاهتمام ظهور جانبا من جوانب الاعجاز في القرآن الكريم، إذ يؤنث فيه المذكر، ويذكر فيه المؤنث، ويخبر عن أحداهما بالأخر. ساهمت هذه القضية في بيان الأسرار البلاغية بالنص القرآني، وبيان أوجه الدلالية المتنوعة، وأثر ذلك في استنباط الاحكام. وهي ظاهرة استعان بها العلماء لجمع شتات الفروع التي يبدو ظاهرها متنافرا ومخالفا للقاعدة بغرض ارجاعها للقاعدة واخضاعها للسياق. ويعد القرن الرابع الهجري أهمية خاصة فيما يتعلق بهذا التراث اللغوي القرآني المهم، إذ ظهرت فيه أهم مصنفات هذا التراث كمعاني القرآن وأعرابه للزجاج والنحاس.
The study of the phenomenon of reminders and Tanith of important grammatical studies, because of their significant impact in the syntax of the sentence, a requirement is necessary for specialists in linguistic studies, and the importance of this phenomenon has received the attention of linguists, a phenomenon agreed by scientists, The aspects of miracles in the Holy Quran, where the masculine feminine, and mention the feminine, and tell each other This case contributed to the statement of the rhetorical secrets in the Qur'anic text, and the statement of various aspects, and the effect of this in the development of judgments. A phenomenon used by scientists to collect the sects of branches that appear to be inconsistent and contrary to the rule for the purpose of returning to the rule and subject to the context The fourth century AH is especially important in relation to this important linguistic heritage of the Koran, as it featured the most important works of this heritage, such as meanings of the Koran and its lover of glass and copper
Keywords: الأدب العربى -- البلاغة العربية -- التعريف -- التنكير -- القرآن الكريم